Leverage and GCG Effects on Financial Performance Moderated by Firm Size - Yudhanto, Wildan; Sadewo, Satrio Tegar; Giovanni, Axel; Ananda, Emmaculata Sac Cid; Sijabat, Yacobo P. (LifeSciFi, 2025)
This research aims to empirically analyze the influence of leverage and Good Corporate Governance (GCG) on financial performance, with firm size functioning as a moderating variable, specifically within the hospitality industry in a Regency. The hospitality sector is a crucial part of the service industry that needs to be developed to foster new opportunities and enhance performance through competitive advantages. Employing a mixed methods approach, the study utilized purposive sampling to select a total of 117 industry units. Data analysis was conducted using the Moderated Regression Analysis (MRA) method. The results reveal that firm size does not moderate the effect of leverage on financial performance. Nonetheless, the GCG components namely the size of the board of directors, board of commissioners, and institutional ownership demonstrate a significant impact on financial performance when firm size is used as a moderating factor. Based on these findings, it can be concluded that effective implementation of GCG elements, supported by firm size, can strengthen financial performance in the hospitality industry. However, firm size alone is insufficient to influence the relationship between leverage and performance in this sector.